PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA INTERAKTIF BERBASIS POWERPOINT DIKOMBINASIKAN DENGAN ISPRING SUITE DI KELAS IV SEKOLAH DASAR - Bibit Lestari; Andrijati, Noening (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Interactive learning media can be used by educators in learning to increase student activeness and learning outcomes. This type of research is Research and Development (R&D) using the ADDIE model. This development aims to test the feasibility, practicality, and effectiveness of Powerpoint-based Interactive Mathematics Learning Media Combined with Ispring Suite to improve student learning outcomes. This research was conducted from February to April 2024. Qualitative data and quantitative data are the types of data used in this study The population in this study were fourth grade students totaling 25 students. Product trials were carried out in small-scale groups at SDN Ngijo 02 and large-scale groups at SDN Ngijo 01. Data collection techniques used tests, namely pretests and posttests and non-tests, namely observation, questionnaires, and interviews. The results of validation by material experts and media experts received 91.25% and 90% respectively with very feasible criteria. Based on the results of the pretest and posttest of the large-scale group, the N-Gain value was 0.586 in the medium category with a percentage of effectiveness of 58.6%. Based on the results of teacher and student responses, the large-scale group obtained 100% and 88.9% respectively with very positive criteria. Based on these results, it can be concluded that the Powerpoint-Based Interactive Mathematics Learning Media Combined with iSpring Suite is feasible, effective, and practical to use in improving student learning outcomes in grade IV.